Предмет: Алгебра, автор: пингвин26

x квадрат - 4 ( х-2) +3х -14=0
4 х квадрат-3 (х квадрат -2х)-10=6
5 х квадрат -3 (х квадрат +2х) +3х+9=14
(2х+3)(3х+1)-10=11х+20
Пожалуйста, помогите!

Ответы

Автор ответа: skvrttt
0
1–е уравнение: 
x^2-4(x-2)+3x-14=0\x^2-4x+8+3x-14=0\x^2-x-6=0\sqrt{D}=sqrt{(-1)^2-4*1*(-6)}=sqrt{1+24}=sqrt{25}=5\x_1=frac{1+5}{2}=3\x_2=frac{1-5}{2}=-2

2–е уравнение: 
4x^2-3(x^2-2x)-10=6\4x^2-3x^2+6x-10=6\x^2+6x-16=0\sqrt{D}=sqrt{6^2-4*1*(-16)}=sqrt{36+64}=sqrt{100}=10\x_1=frac{-6+10}{2}=2\x_2=frac{-6-10}{2}=-8

3–уравнение: 
5x^2-3(x^2+2x)+3x+9=14\5x^2-3x^2-6x+3x+9=14\2x^2-3x-5=0\sqrt{D}=sqrt{(-3)^2-4*2*(-5)}=sqrt{9+40}=sqrt{49}=7\x_1=frac{3+7}{4}=2,5\x_2=frac{3-7}{4}=-1

4–е уравнение: 
(2x+3)(3x+1)-10=11x+20\6x^2+2x+9x+3=11x+30\6x^2=27\x^2=4,5\x=бsqrt{4,5}
Похожие вопросы
Предмет: Химия, автор: kiruxa1122hh